Bromocriptine improves glucose tolerance independent of circadian timing, prolactin, or the melanocortin-4 receptor - Framnes-DeBoer, Sarah N. (Am J Physiol Endocrinol Metab, 2020)
Bromocriptine, a dopamine D2 receptor agonist originally used for the treatment of hyperprolactinemia, is largely successful in reducing hyperglycemia and improving glucose tolerance in type 2 diabetics. However, the mechanism behind bromocriptine’s effect on glucose intolerance is unclear. Here, we tested three hypotheses, that bromocriptine may exert its effects on glucose metabolism by 1) decreasing prolactin secretion, 2) indirectly increasing activity of key melanocortin receptors in the central nervous system, or 3) improving/restoring circadian rhythms. Using a diet-induced obese (DIO) mouse model, we established that a 2-wk treatment of bromocriptine is robustly effective at improving glucose tolerance. We then demonstrated that bromocriptine is effective at improving the glucose tolerance of both DIO prolactin-deficient and melanocortin-4 receptor (MC4R)-deficient mice, pointing to bromocriptine’s ability to affect glucose tolerance independently of prolactin or MC4R signaling. Finally, we tested bromocriptine’s dependence on the circadian system by testing its effectiveness in environmental (e.g., repeated shifts to the light-dark cycle) and genetic (e.g., the Clock mutant mouse) models of circadian disruption. In both models of circadian disruption, bromocriptine was effective at improving glucose tolerance, indicating that a functional or well-aligned endogenous clock is not necessary for bromocriptine’s effects on glucose metabolism. Taken together, these results do not support the role of prolactin, MC4R, or the circadian clock as integral to bromocriptine’s underlying mechanism. Instead, we find that bromocriptine is a robust diabetic treatment and resilient to genetically induced obesity, diabetes, and circadian disruption.